mef2ca and mef2cb Double mutant Zebrafish show altered craniofacial phenotype and motor behaviour - Adrião, Andreia (2023)
The transcription factor MEF2C is crucial in neuronal, cardiac, bone and cartilage molecular processes, as well as for craniofacial development. MEF2C was associated with the human disease MRD20, whose patients show abnormal neuronal and craniofacial development. Zebrafish mef2ca;mef2cb double mutants were analysed for abnormalities in craniofacial and behaviour development through phenotypic analysis. Quantitative PCR was performed to investigate the expression levels of neuronal marker genes in mutant larvae. The motor behaviour was analysed by the swimming activity of 6 dpf larvae. We found that mef2ca;mef2cb double mutants display several abnormal phenotypes during early development, including those already described in zebrafish carrying mutations in each paralog, but also (i) a severe craniofacial phenotype (comprising both cartilaginous and dermal bone structures), (ii) developmental arrest due to the disruption of cardiac oedema and (iii) clear alterations in behaviour. We demonstrate that the defects observed in zebrafish mef2ca;mef2cb double mutants are similar to those previously described in MEF2C-null mice and MRD20 patients, confirming the usefulness of these mutant lines as a model for studies concerning MRD20 disease, the identification of new therapeutic targets and screening for possible rescue strategies.